2001
DOI: 10.1109/23.983179
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced leakage currents: atomic scale mechanisms

Abstract: We link atomic-scale defects called E′ centers to radiation-induced leakage current (RILC). We present evidence that strongly suggests that RILC tolerance is processing dependent and that this tolerance appears to be correlated with lower E′ center generation. We furthermore note that in oxides subjected to quite high irradiation levels, the density of (generally electrically neutral) E′ centers is far greater than would be expected for the hole trap E′ centers involved in the radiation-induced positive charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Ceschia et al 2 suggested that the traps/defects involved in the electron conduction are neutral; however, these defects likely have a positively charged precursor. Candidates for precursor defects include hole traps ͑such as an EЈ center, 10 which becomes neutralized after capturing a hole͒; however, the microscopic character of the traps/defects involved in the process is not yet resolved. It has been suggested that both RILC and SILC originate from the same defect.…”
Section: Resultsmentioning
confidence: 99%
“…Ceschia et al 2 suggested that the traps/defects involved in the electron conduction are neutral; however, these defects likely have a positively charged precursor. Candidates for precursor defects include hole traps ͑such as an EЈ center, 10 which becomes neutralized after capturing a hole͒; however, the microscopic character of the traps/defects involved in the process is not yet resolved. It has been suggested that both RILC and SILC originate from the same defect.…”
Section: Resultsmentioning
confidence: 99%
“…6. The mechanism for this increase has been mainly attributed to the trap-assisted inelastic tunneling process [13]. With the positive bias at the gate terminal, the electrons can tunnel to the oxide traps and then to the gate electrode.…”
Section: ) Radiation-induced Gate Leakage Currentmentioning
confidence: 99%
“…Ceschia et al suggested that the traps/defects involved in the electron conduction are neutral; however, these defects likely have a positively charged precursor [2]. Candidates for precursor defects include hole traps (such as an center [14], which becomes neutralized after capturing a hole); however, the microscopic character of the traps/defects involved in the process is not yet resolved. It has been suggested that both RILC and SILC originate from the same defect [15].…”
Section: B Leakage Mechanisms In Oxidesmentioning
confidence: 99%